BEHAVIORISTIC LEARNING THEORY AND STUDENT MOTIVATION: IMPLICATIONS FOR ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Ramli; Haryani, Ninik; Wahyuni, Fitri (EDUCATIONE, 2024)
The Covid-19 pandemic has profoundly impacted education in Indonesia, necessitating the adoption of distance learning strategies. This shift, initially prompted by the pandemic's spread, introduced challenges such as decreased student motivation, technical hurdles, and digital disparities. Drawing upon Behavioristic Learning Theory, which emphasizes stimulus-response dynamics and reinforcement, it becomes evident that student motivation is pivotal in the learning process. During the pandemic, online learning witnessed fluctuations in student motivation, initially marked by heightened interest but later dampened by challenges like poor internet connectivity. Moreover, the transition from face-to-face to online learning underscored the significance of external factors, including the learning environment and support systems, in shaping student motivation. Government initiatives to address these challenges included providing online platforms, internet quotas, and adjusting learning policies. While online learning proved effective during the pandemic, it also highlighted the need for innovative approaches to sustain student engagement and motivation. Factors like parental involvement, teacher creativity, and student interest emerged as crucial determinants of motivation. As education continues to evolve, there is a pressing need to adapt learning strategies to meet diverse student needs, whether through online, offline, or hybrid approaches. Fostering intrinsic motivation and creating supportive learning environments remain paramount for ensuring optimal learning outcomes amidst the challenges posed by the pandemic and beyond.